The Influence Of Instagram Micro-Influencers Factor Toward Customer’s Interest And Intention To Visit In Tourism Sectors - Dea Cahyani (CV. Syntax Corporation Indonesia, 2023)
One of the main industries is tourism. The number of islands in Indonesian waters is 17,508, according to information we found online. As a result, social media also have an impact on the tourism sector, particularly on how tourists access and use information about the destination for their travel planning activities. This presents important challenges for tourism marketers when it comes to swaying consumers' attitudes, perceptions, and intentions to use a product or service. According to earlier study, a lot of tourism-related sectors currently employ influencer marketing as a marketing tactic to advertise a particular tourist destination. Important Performance Analysis and Structural Equation Modelling are two quantitative methods used in this study to collect data. The samples consist of 217 respondents, who are between the ages of 18 and 35, Indonesians who enjoy travelling, backpacking, or going solo, and who are based in the areas of Jakarta, Bogor, Depok, Tangerang, Bekasi, and Bandung. The goal of this study is to identify the marketing strategy when using micro-influencer marketing based on the indicators of consideration and preferences of micro-influencer marketing based on the credibility, trustworthiness, attitude of the influencer towards the content, and photography and videography that can significantly positively influence effects to the customer interest and visit intentions. As a result, this study also looks at possible marketing strategies for Singgah businesses or other businesspeople operating in this sector. The tourism industry is anticipated to benefit from this study.